2000
DOI: 10.1038/sj.ejhg.5200515
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of CAG and CCG repeats in Huntingtin gene among HD patients and normal populations of India

Abstract: We have analysed the distribution of CAG and adjacent polymorphic CCG repeats in the Huntingtin gene in 28 clinically diagnosed unrelated Huntington's disease (HD) patients and in normal individuals belonging to different ethnic groups of India. The range of expanded CAG repeats in HD patients varied from 41 to 56 repeats, whereas in normal individuals this number varied between 11 and 31 repeats. We identified six CCG alleles from a total of 380 normal chromosomes that were pooled across different ethnic popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
32
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 21 publications
7
32
0
Order By: Relevance
“…27 In our sample, as in others, 22,23 the (CCG) 6 and (CCG) 8 alleles were rare. In Portuguese, Indian and Japanese populations, 23,27,28 multiple CCG alleles were associated with expanded CAG repeats within individual families. These findings suggest that one mutational event may have led to these differences in the number of CCG repeats.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…27 In our sample, as in others, 22,23 the (CCG) 6 and (CCG) 8 alleles were rare. In Portuguese, Indian and Japanese populations, 23,27,28 multiple CCG alleles were associated with expanded CAG repeats within individual families. These findings suggest that one mutational event may have led to these differences in the number of CCG repeats.…”
Section: Discussionsupporting
confidence: 78%
“…The CCG polymorphic region may indicate the ancestral origin of the expanded CAG repeat allele that causes HD, 21 given that they are located in the same chromosomal region, only 12 bp apart. Each ethnic population shows a predominance of a certain number of CCG repeats that can vary from 6 to 12 repeats, 22 with the exception of a case reported by Pramanik et al, 23 in which four CCG repeats were identified.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the CAG repeat region among 44 HD patients (39-66 CAGs) and 51 normal individuals (9-34 CAGs) showed that the range of the repeat size was similar to previous reports in other populations (Andrew et al, 1993;Huntington's Disease Collaborative Research Group, 1993;Andrew and Hayden, 1995;Brandt et al, 1996;Pramanik et al, 2000). In addition, the mean CAG size of 102 normal chromosomes of Croatian origin (18.5 ± 3.5) was found to resemble that for a Western European populations (18.4 ± 3.7) and was considerably higher than the mean CAG lengths found on Black, Chinese, Japanese and Finnish normal chromosomes (16.5 ± 1.7) (Squitieri et al, 1994).…”
Section: Discussionsupporting
confidence: 84%
“…In this respect, populations of Western European descent, that have a higher prevalence rate of HD, have a higher frequency of the CCG allele 7, while in African Blacks, Japanese, Chinese and Finnish populations, where HD occurs more rarely, the CCG allele 10 is overpresented (Squitieri et al, 1994;Andrew and Hayden, 1995;Pramanik et al, 2000). In addition, the ∆2642 polymorphism which is not found at all in African and Asian populations is overpresented among HD cases of W. European descent Andrew and Hayden, 1995).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation